Dissemination of village archive management as a historical source - Melisa Prawitasari; Wisnu Subroto; Fathurrahman Fathurrahman; Imbar Desi Mutri Yanti (Community Empowerment, 2021)
The community service provided in Karang Indah Village aims to disseminate and assist village officials in preparing archives. This activity involves students of the History Education study program as the implementation of archival and museum science. The preparation of archives, both manually and digitally, is very important for all agencies, especially in the village office. This is done, of course, to make it easier to serve the community. When needed, archives that have been well organized will be easy to find. Archives contain primary data and play an important role in the process of reconstructing history. The archive's position is so critical that it must be managed properly and appropriately. The implementation method consists of three steps: planning, implementation, and evaluation. The service activities have resulted in increased knowledge and skills among village officials in the preparation and management of archives, both manually and digitally.